The relationship between home- and individual-level diet quality among African American and Hispanic/Latino households with young children - Kong, Angela (Int J Behav Nutr Phys Act, 2018)
BACKGROUND: The quality of most Americans’ diets is far from optimal. Given that many Americans consume a significant portion of calories in the home, intervening in this setting could be beneficial. However, the relationship between the home food environment and diet quality is not well understood. This study examined the relationship between diet quality at the individual level with home-level diet quality using an index that measures compliance with federal dietary guidance. METHODS: This was a cross sectional study that enrolled 97 African American and Hispanic/Latino low-income parent-child dyads. Diet quality at the individual level was assessed through two 24-h dietary recalls collected for parents and children, respectively. Diet quality at the home level was assessed with two home food inventories conducted in participants’ homes. Diet quality scores at the home and individual levels were computed by applying the Healthy Eating Index-2010 (HEI-2010) to these data. Linear models adjusted for potential confounding factors were used to examine the relationship between diet quality at the home and individual levels. RESULTS: Total HEI-2010 scores from parents and children’s diets were positively associated with HEI-2010 scores based on home food inventories (parent diet: β: 0.36, 95% CI: 012–0.60; child diet: 0.38 95% CI: 013–0.62). Positive associations were also observed between individual level and home level subcomponent HEI-2010 scores for total fruit (parent: 0.55 95% CI: 0.16–0.94; child: 0.49 95% CI: 0.03–0.94), whole fruit (parent only: 0.41 95% CI: 0.07–0.74), greens and beans (parent only: 0.39 95% CI: 0.05–0.74), and whole grain (children only: 0.33 95% CI: 0.04–0.63). CONCLUSION: This study demonstrated that individual level diet quality was positively associated with home-level diet quality. Findings from this study can help us to address modifiable targets of intervention in the home to improve diet quality.